Quality of life, depression and anxiety among pregnant women with previous adverse pregnancy outcomes - Couto, Evelyn Regina; Couto, Egle; Vian, Bruna; Gregório, Zoraide; Nomura, Marcelo Luis; Zaccaria, Renata; Passini Junior, Renato (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Previous adverse pregnancy outcomes (recurrent spontaneous abortion, fetal death, preterm birth or early neonatal death) can affect the quality of life of pregnant women. The objective of this study was to compare the quality of life and the prevalence of symptoms of anxiety and depression among pregnant women with and without these antecedents. DESIGN AND SETTING: An analytical cross-sectional study was performed in four settings (two high-risk and two low-risk prenatal clinics) in the city of Campinas, São Paulo, Brazil. METHODS: A total of 240 women were interviewed by a single investigator between the 18th and 24th weeks of gestation: 120 women with prior adverse pregnancy outcomes (group 1) and 120 women with no such history (group 2), matched according to their numbers of living children. Sociodemographic variables were collected and two questionnaires were used: the Short Form-36 quality-of-life questionnaire and the Depression and Anxiety Scale. RESULTS: The women in group 1 had lower scores in all the items on the quality-of-life questionnaire. Depression and anxiety were more frequent in group 1 (P < 0.0001). An inverse correlation was found between the Short Form-36 domains and anxiety and depression. CONCLUSIONS: Women with histories of recurrent spontaneous abortion, fetal death, preterm birth or early neonatal death seem to have poorer quality of life and more symptoms of anxiety and depression during their subsequent pregnancy, compared with those without such antecedents.